Design of the 3D Printhead with Extruder for the Implementation of 3D Printing from Plastic and Recycling by Industrial Robot - Martin Pollák (TEM Journal, 2019)
This paper deals with the design of the printhead prototype with extruder which serves for universal processing using several types of materials. It briefly describes the basic principles of FDM technology for which the prototype is designed. The main goal is to explore the possibility of combining 3D printing, and robot technology in order to design a universal printhead, capable of printing from plastic, recycled materials and other substances, including the composites. The proposed concept allows printing oversized objects that are not limited by the relatively small working space compared to commercial FDM devices.